Public Debt Management and Macroeconomic Stability : An Overview - Montiel, Peter J. (Oxford University Press on behalf of the World Bank, 2013)
Recent research suggests that management of the public sector debt can have important effects on a country macroeconomic performance. This Public debt management and macroeconomic stability article provides an overview of the factors that the recent literature has identified as important in determining the optimal composition of the public debt. Based on this analysis, it attempts to establish general guidelines for public debt management in emerging economies. To retain market access and promote domestic financial market development, governments should generally finance themselves at market rates using a wide variety of securities. Beyond this general principle, the optimal composition of the public debt involves a tradeoff between enhancing the government anti-inflationary credibility and reducing the vulnerability of its budget to macroeconomic shocks. Consequently, the optimal composition of the debt depends on a country circumstances. Debt should be heavily weighted toward long-term nominal securities for governments that have anti-inflationary credibility and toward long-term indexed debt for those that do not.